2022
DOI: 10.1088/1755-1315/1107/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Implications of using fermentation plant extract formulations against pests and predator in rice plants

Abstract: Currently the use of plant extracts to reduce pest attacks is a concern. Mixed formulation of two plant extracts Calatropis gigantea and Crescentia cujete was applied in the filed rice to assess the effectiveness of these formulations in reducing insect pest populations and predatory (natural enemies). The results showed that the combination of C. gigantea and C. cujete in one formulation could reduce the population of the main pests of rice plants and did not affect the presence of natural enemies (predators)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Tannin compounds can affect insects in terms of oviposition, flavonoid compounds can inhibit the transport of leucine amino acids and are toxic to insects [22]. Previous research shown a synergistic impact between C. gigantea and C. cujete in preventing the growth of Scirpophaga innotata and Cnaphalocrosis medinalis [24]. Based on this research, a mixture of fermented C. gigantea and C. cujete was used to reduce pests and the effects it had on natural enemies, particularly rice plant predators.…”
Section: Introductionmentioning
confidence: 97%
“…Tannin compounds can affect insects in terms of oviposition, flavonoid compounds can inhibit the transport of leucine amino acids and are toxic to insects [22]. Previous research shown a synergistic impact between C. gigantea and C. cujete in preventing the growth of Scirpophaga innotata and Cnaphalocrosis medinalis [24]. Based on this research, a mixture of fermented C. gigantea and C. cujete was used to reduce pests and the effects it had on natural enemies, particularly rice plant predators.…”
Section: Introductionmentioning
confidence: 97%
“…Although renowned for its pharmacological properties, the potential of majapahit as an insecticide is still limited [8]. Previous research has documented deterrent, anti-feedant, and toxic activities of C. cujete against rice pests and livestock ticks [9,10]. This study aims to assess the efficacy of C. cujete fruit extract in mitigating S. litura infestation in crops, utilizing the Chinese mustard plant as a model.…”
Section: Introductionmentioning
confidence: 99%